CoS2 needle arrays induced a local pseudo-acidic environment for alkaline hydrogen evolution. Issue 32 (28th July 2021) - Chen, Guozhu; Li, HuangJingWei; Zhou, Yajiao; Cai, Chao; Liu, Kang; Hu, Junhua; Li, Hongmei; Fu, Junwei; Liu, Min
Abstract : Finite-element simulations and direct detection of local pH changes prove that local C(OH − ) can be regulated to form a local pseudo-acidic environment by LEF, which greatly promote H2 O dissociation for better alkaline HER performance. Abstract : The alkaline electrocatalytic hydrogen evolution reaction (HER) is a potential way to realize industrial hydrogen production. However, the sluggish process of H2 O dissociation, as well as the accumulation of OH − around the active sites, seriously limit the alkaline HER performance. In this work, we developed a unique CoS2 needle array grown on a carbon cloth (NAs@C) electrode as an alkaline HER catalyst. Finite-element simulations revealed that CoS2 needle arrays (NAs) induce stronger local electric field (LEF) than CoS2 disordered needles (DNs). This LEF can greatly repel the local OH − around the active sites, and then promote the forward H2 O dissociation process. The local pH changes of the electrode surface confirmed the lower OH − concentration and stronger local pseudo-acidic environment of NAs@C compared to those of DNs@C. As a result, the NAs@C catalyst exhibited a low HER overpotential of 121 mV at a current density of 10 mA cm −2 in 1 M KOH, with the Tafel slope of 59.87 mV dec −1 . This work provides a new insight into nanoneedle arrays for the alkaline HER by electric field-promoted H2 O dissociation.